Pengungkapan Kinerja Sosial Perbankan Syariah di Indonesia - Darihan Mubarak; Sigit Pramono; Ai Nur Bayinah (Jurnal Akuntansi dan Keuangan Islam, 2019)
The research aims to determine the disclosure of the social performance of Islamicbanking based on the ISR index. The method used in this research is qualitativecontent analysis. Qualitative content analysis is also called Ethnographic ContentAnalysis (ECA), which is a combination of objective content analysis and participantobservation where researchers interact with documentation materials. The populationin this study are all Islamic Commercial Banks (BUS) in Indonesia with a sample ofBUS which has published annual reports for the 2015-2017 period using purposivesampling method. From the assessment results using the ISR index, it was found thatBSM occupies the highest disclosure value in the 2015-2017 period. The average peryear shows that the reporting of social performance of Islamic Bank tends to increasewith a good predicate.